A novel mutation of the C-terminal amino acid of FUS (Y526C) strengthens FUS gene as the most frequent genetic factor in aggressive juvenile ALS. Issue 3 (3rd April 2017) - Corcia, Philippe; Danel, Veronique; Lacour, Arnaud; Beltran, Stephane; Andres, Christian; Couratier, Philippe; Blasco, Helene; Vourc'h, Patrick
Abstract: Although amyotrophic lateral sclerosis (ALS) typically occurs around 60 years, numerous publications report an onset of ALS before the age of 25 years that define juvenile ALS (jALS). Over the last decade, growing literature mentioned jALS with an aggressive evolution which are mainly linked to the FUS gene. We report here the case of a 25-year-old woman with a bulbar onset ALS that progressed in less than 12 months to invasive ventilation due to respiratory failure; Genetic screening identified a new mutation in the FUS gene that lies within the last codon. After reading the literature, it might be legitimate to consider that jALS linked to FUS mutations represent a specific entity different from both classical jALS and adult ALS linked to FUS gene. This should encourage clinician to firstly screen the FUS gene in the presence of a sporadic ALS that occurs before the age of 25 and with an aggressive profile of evolution.